2014
DOI: 10.1536/ihj.13-231
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged PR Interval and Risk of Recurrence of Atrial Fibrillation After Catheter Ablation

Abstract: SummaryIt has been demonstrated that a prolonged PR interval is associated with an increased risk of AF. However, the impact of a prolonged PR interval on recurrence of paroxysmal atrial fi brillation (AF) after catheter ablation is not clear. A total of 112 patients with a prolonged PR interval (PR > 200 ms) (PPR group) and 112 age-and gender-matched control patients (on a 1:1 basis) with a normal PR interval (NPR group) were included in this study. AF recurrence was defi ned as the occurrence of confi rmed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Several work groups found a close connection between prolonged PR interval using the clinical definition of first-degree AVB (PR >200 ms) and incidence of AF as well as other adverse cardiovascular outcomes like stroke, heart failure and dementia causing an increased mortality [ 3 , 4 , 13 ]. Besides the association between PR interval prolongation with onset of AF [ 5 ], higher recurrence rates after catheter ablation were described [ 6 , 14 ]. However, there are also studies that could not show an association between prolonged PR interval and AF [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several work groups found a close connection between prolonged PR interval using the clinical definition of first-degree AVB (PR >200 ms) and incidence of AF as well as other adverse cardiovascular outcomes like stroke, heart failure and dementia causing an increased mortality [ 3 , 4 , 13 ]. Besides the association between PR interval prolongation with onset of AF [ 5 ], higher recurrence rates after catheter ablation were described [ 6 , 14 ]. However, there are also studies that could not show an association between prolonged PR interval and AF [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under such physical or mental condition, conducting V-pacing because of DDDR (CLS)-mode with rate-dependent stepwiseshortening AV sequence, rather than preventing V-pacing, might have effectively reduced the atrial overload and improved the atrial vulnerability to AF exclusively during rapid pacing over 90 bpm in our case. Other population-based studies conducted under the condition of ambulatory daily life have shown that a PQ interval longer than 200 ms was associated with development of AF, [12][13][14] which also suggested that extreme AV prolongation along with diastolic mitral regurgitation might have resulted in atrial overload and be associated with atrial vulnerability to PAF.…”
Section: Discussionmentioning
confidence: 93%
“…20,21) Although many patients with late recurrence after PAF ablation had reconnected PVs, a smaller percentage of patients undergoing repeat procedures for AF recurrence were found to have non-PV foci that may not have been identified or targeted during the initial procedure. 22) About 4% to 42% of patients having repeat ablation procedures for paroxysmal AF need ablation of non-PV foci during the follow-up procedure.…”
Section: Discussionmentioning
confidence: 99%